Strength and durability analysis of a flat spring at vibro-impact loadings - Gursky, Volodymyr; Kuzio, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
Volodymyr Gursky, Igor Kuzio We present the scheme of realization of a vibroimpact system with one flat spring and locally focused mass. The means of implementation of asymmetric piecewise linear elastic characteristic is the use of two intermediate cylindrical supports. We calculated the bending and contact stresses that take into account the asymmetry of change in the elastic characteristic and instantaneous displacement of the local mass. The parametric dependency is taken into account of the contact rigidity between the cylindrical support and the flat spring on the displacement of the local mass. This is carried out in order to assess in the course of dynamic analysis the stressed state of a flat spring under conditions of implementation of elastic characteristic. The contact rigidity is taken into account through the change in own oscillations frequency of the spring. We numerically solved the dynamic problem and obtained the ratio between kinematic characteristics (displacement and acceleration) and parameters of the stressed state (bending and contact stresses). The contact stresses are nonlinearly dependent on displacement, the bending –linearly. The strength margin factors by the stresses were defined, as well as the equivalent strength margin factor and the lifetime of the rod as the function of effort of perturbation. The equivalent strength margin factor takes into account the joint action of bending asymmetric and contact stresses. The obtained formulas realize the method of analysis of the stressed state under conditions of vibroimpact loadings. The method may be successfully applied in the course of design and synthesis of resonant vibroimpact systems and modes.